2021
DOI: 10.1016/j.jsams.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary incontinence among elite athletes of both sexes

Abstract: Objectives: To determine the prevalence of urinary incontinence (UI) among elite athletes and to compare prevalences between sexes and across different sports modalities. Methods: This was a cross-sectional, observational study conducted in 754 elite athletes (455 women or girls and 299 men or boys). Participants completed a questionnaire to collect self-reported anthropometric measures, medical history and sport-related data, and the questionnaires International Consultation on Incontinence Questionnaire-UI S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
5
20
0
Order By: Relevance
“…Strenuous exercise has been cited as a risk factor for developing symptoms of SUI [ 14 ]. The pooled data confirmed that SUI was the most prevalent type, according to previous findings in female athletes [ 39 ] and among women who exercised regularly [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…Strenuous exercise has been cited as a risk factor for developing symptoms of SUI [ 14 ]. The pooled data confirmed that SUI was the most prevalent type, according to previous findings in female athletes [ 39 ] and among women who exercised regularly [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…The training routines of athletes specialized in sprint or hurdles events are very different from those of athletes specializing in throwing or jumping events, among others. Although very few studies to date have analyzed the prevalence of UI in track and field athletes [ 7 , 12 ], authors have shown an especially high prevalence in these events [ 12 ]. Sporting activities from track and field could be damaging the perineal structures and facilitating UI, particularly in athletes who periodically perform high-intensity training, such as elite athletes.…”
Section: Introductionmentioning
confidence: 99%
“…While women athletes are unlikely to seek medical attention for their UI or disclose the health condition to their coaches, they do believe that UI should not be left to them to manage alone [ 21 ]. Professionals who support women athletes therefore need to be aware of the prevalence of UI and its implications [ 22 ] to ensure early identification of athletes who are at risk, enabling early, quality treatment and interdisciplinary clinical collaboration [ 23 ].…”
Section: Introductionmentioning
confidence: 99%